Empirical Insight: Religious Moderation Within the Family Context – Unveiling Research Findings - Anto, Abdul Haris Fitri; Husna, Atinal; Pramesti, Mei Dwi; Zulfahmi, Najib; Dewi, Shafira Rahma (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
This article seeks to chart the outcomes of empirical research on religious moderation within the family. The issue behind this research arises from the dearth of publications that accentuate the findings of empirical studies in this domain. The primary objective is to comprehend previous discoveries and lay the groundwork for subsequent empirical investigations into the theme of religious moderation within the family. Employing the scoping review to achieve the research objective, this research explicitly targets empirical articles concerning family religious moderation. The literature search on Google Scholar focuses on publications spanning the past decade (2013-2023). The selection of literature adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Following these guidelines, 18 articles were chosen for comprehensive review. The results of the research polarise on three key themes, including religious moderation within the family, fostering tolerance and non-violence values, as well as religious moderation education. Although the existing empirical research about religious moderation remains limited and widely open for further research, it can be concluded that it forms the foundational bedrock for cultivating robust and tolerant relationships within the family.